Structural and microstructural study of the alloy AlxFe(1-x) (x=0.25, 0.5 y 0.75) obtained by arc furnace - Rocha Cabrera, R. (2021)
The Fe-Al alloys in the compositions Al25Fe75, Al50Fe50 and Al75Fe25 were synthesized by the technique from arc furnace and then heat treated at 6000C. The X-ray diffractogram (XRD) and Mössbauer spectroscopy (MS) show the formation of the intermetallic FeAl and Al13Fe4 for the compositions Al50Fe50 and Al75Fe25 and the solid solution Fe(Al) rich and poor in iron for all the compositions.